(untitled) (Bangladesh Journal of Child Health, 2018)
Background: Recurrent and persistent pneumonia have become a challenge for the physicians. The aim of this study was to evaluate the clinical profile and determine the underlying causes of recurrent and persistent pneumonia among the children admitted in Dhaka Shishu (Children) Hospital. Methods: In this study, retrospective analysis of medical records of the children was done, who met the criteria of recurrent pneumonia and persistent pneumonia. Analyzed Patients were admitted in Dhaka Shishu (Children) Hospital from January 2016 to Decembe 2016. Results: A total of 30 patients were analyzed during the study period. Twenty-four patients presented with recurrent pneumonia (80%) and six patients presented with persistent pneumonia (20%) during the study a period. After analysis of clinical profile, identified causes were pulmonary TB (23.3%), congenital heart disease (13.3%), cystic fibrosis (16.6%), aspiration syndrome (13.3%), bronchial asthma (10%), immune deficiency disorders (10%), bronchiectasis (6.6%), congenital lung agenesis (3.3%), unknown cause (3.3%). Conclusion: The most frequent underlying cause for recurrent and/or persistent pneumonia was pulmonary TB followed by congenital heart disease and cystic fibrosis among the patients admitted in Dhaka Shishu (Children) Hospital. Bangladesh J Child Health 2018; VOL 42 (3) :125-129